2020
DOI: 10.3390/ijerph17239110
|View full text |Cite
|
Sign up to set email alerts
|

The Spillover Influence of Household Waste Sorting on Green Consumption Behavior by Mediation of Environmental Concern: Evidence from Rural China

Abstract: The spillover effect of environmental behavior has been of wide concern in recent years. The purpose of this paper is to explore the influence of household waste sorting on green consumption (behavioral spillover) and the possible psychological mechanisms involved in such spillover of environmental concern. Though it is important, insufficient attention has been paid to exploring the relationship, and the process of its formation, between waste sorting and green consumption. To narrow this gap, survey data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Limited or missing environmental quality information has a particular impact on households' housing choices, thereby affecting their exposure to biological pollution and household welfare. Domestic households are more exposed to pollution and are more harmed when there is a shortage of quality environmental information [47].…”
Section: Eid and Pebmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited or missing environmental quality information has a particular impact on households' housing choices, thereby affecting their exposure to biological pollution and household welfare. Domestic households are more exposed to pollution and are more harmed when there is a shortage of quality environmental information [47].…”
Section: Eid and Pebmentioning
confidence: 99%
“…PEC has an intermediary influence on personal experience of environmental protection intention [58]. In addition, environmental concerns have been shown to mediate the relationship between waste sorting and green consumption behavior [22,38,47,59]. On the other hand, public environmental concerns have been proven to have no significant impact on people's environmental participation [60].…”
Section: Pec and Pebmentioning
confidence: 99%
See 1 more Smart Citation
“…The participation of farmers is an indispensable link for improving the efficiency of rural domestic waste classification [ 6 ]. Farmers are not only the producers and victims of rural domestic waste but also the direct beneficiaries of governance effects.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that people’s past PEBs can promote future PEBs. For example, a study on Chinese consumer behaviour shows that household waste sorting promotes green consumption behaviour [ 2 ]. In addition, when people recall the past PEB, they show higher pro-environmental intentions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%